REDRESSIVE ACTIONS FOLLOWING COMMISERATIONS IN ONLINE DISCUSSIONS - Trávníková, Petra (Verbum, 2018)
In Brown and Levinson’s (1978) seminal classification of positive politeness strategies, commiserating is listed in the subgroup referred to as human-relations wants. The qualitative and quantitative analysis of a corpus consisting of five Internet discussion boards has shown that it is also one of the most frequent positive politeness strategies used there. All the threads under examination are dedicated to the so-called women’s topics, such as dieting, pregnancy, infertility or mothering. The members of these close-knit communities formed upon the boards find it necessary to express sympathy in order to enhance each other’s (positive) face and avoid face-threatening acts arising from the sensitive nature of these topics. However, the analysis of the corpus has also revealed that to commiserate merely by saying they are sorry is not enough. The interlocutors find it necessary to add often complex redressive actions to boost the illocutionary force of their statements. Thus the aim of the paper is to explore the formulaic character of commiserations and categorise the numerous redressive actions following them, taking into account their two main functions, i.e. building rapport and facilitating smooth communication within online communities.